2019
DOI: 10.1016/j.clml.2019.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Conditioning Regimens in Allogeneic Hematopoietic Stem-Cell Transplantation Shows Superiority of Total Body Irradiation–Based Regimen for Younger Patients With Acute Leukemia: A Nationwide Study

Abstract: Recognizing the paucity of comparative data on different conditioning regimens for hematopoietic stem-cell transplantation in Asian population, we conducted a study of 1562 patients undergoing myeloablative conditioning (MAC) and 2693 patients undergoing non-MAC (NMC). We found that (1) despite the possible selection bias, MAC is associated with decreased late-phase mortality, (2) among MAC regimens, total body irradiatione based conditioning leads to better outcomes for all acute leukemias in younger patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The recovery to functional blood count levels is prolonged in some patients for various reasons such as advanced age, decreased clearance of chemotherapeutic drugs due to renal or liver dysfunction or concurrent radiotherapy to the bone marrow [ 18 20 ]. For allogeneic hematopoietic stem cell transplantation recipients, a certain degree of immunosuppression is deliberately maintained for 6–12 months after myeloablative chemotherapy for prophylaxis against graft-vs.-host-disease [ 21 ]. For the reasons mentioned above, the primary aim for dental evaluation in patients undergoing anti-neoplastic chemotherapy and hematopoietic stem cell transplantation is to prevent and minimize the occurrence of opportunistic infections and the potential systemic spread of a local infection [ 22 , 23 ].…”
Section: Indicationsmentioning
confidence: 99%
“…The recovery to functional blood count levels is prolonged in some patients for various reasons such as advanced age, decreased clearance of chemotherapeutic drugs due to renal or liver dysfunction or concurrent radiotherapy to the bone marrow [ 18 20 ]. For allogeneic hematopoietic stem cell transplantation recipients, a certain degree of immunosuppression is deliberately maintained for 6–12 months after myeloablative chemotherapy for prophylaxis against graft-vs.-host-disease [ 21 ]. For the reasons mentioned above, the primary aim for dental evaluation in patients undergoing anti-neoplastic chemotherapy and hematopoietic stem cell transplantation is to prevent and minimize the occurrence of opportunistic infections and the potential systemic spread of a local infection [ 22 , 23 ].…”
Section: Indicationsmentioning
confidence: 99%
“…43 When the decision has been made to proceed with an alloSCT, conditioning using myeloablative regimens using total body irradiation (TBI) are preferred in patients with ALL. 44,45 At our center, for Ph−ve ALL, we reserve alloSCT in CR1 (myeloablative conditioning with fludarabine-busulfan) for young (<50 years) and fit patients with one or more conventional high-risk features (high-risk cytogenetics, early thymic precursor [ETP] ALL) only when a matched sibling donor is available. In the absence of a matched sibling donor, these patients are usually treated in the high-risk arm of the BFM-95 protocol.…”
Section: Allosct In Cr1 In Adult Acute Lymphoblastic Leukemiamentioning
confidence: 99%
“…99 In a Korean study, TBI-based conditioning regimens showed favourable outcomes in young adults independent of acute leukaemia subtype (p=0.005). 100 In patients younger than 40 years, TBI provides better 5-year OS (55.1%, p=0.023) and disease-free survival (DFS) (48.6%, p=0.020) outcomes than busulfan-based conditioning regimens. 101 The EBMT Acute Leukaemia Working Party showed that the combination of TBI with etoposide is as effective as combination with cyclophosphamide (HR 0.62, p=0.04).…”
Section: Conditioning Regimens For Allogeneic Haematopoietic Stem Cell Transplantationmentioning
confidence: 99%